Dual opposing actions of STW 5 on TRP receptors mediate neuronal desensitisation in vitro - Khalil, Mohammad; Zhang, Zehua; Abdel-Aziz, H.; Rabini, S.; Ammar, R. M.; Reeh, Peter; Engel, Matthias (Life Sciences, 2020)
Aims: STW 5 is an herbal drug combination used for the treatment of functional gastrointestinal disorders (FGIDs) with visceral hypersensitivity as the therapy-resistant hallmark. STW 5 has been clinically proven to alleviate visceral hypersensitivity-related symptoms, including abdominal pain, bloating, nausea, and early satiety. However, the molecular and cellular mechanisms underlying the antinociceptive action of STW 5 remain unknown. Here, we investigate the role of STW 5 in the calcium mobilisation of dorsal root ganglion (DRG) sensory neurons. Main methods: Calcium imaging experiments were performed with freshly dissociated cultured murine DRG neurons isolated from mice by microfluorometry. TRPA1-deficient DRGs, TRPV1-deficient DRGs, TRPA1/V1 double-deficient DRGs, and wild-type DRGs have been used to investigate the role of TRPs ion channels in mediating STW 5 action. Key findings: STW 5 (1.74 and 5.8 mg/ml) induced calcium ion influx into DRG neurons in a concentration-dependent manner. Calcium transients were desensitised during repeated exposure to STW 5, an effect that was facilitated in TRPA1-deficient DRGs and less pronounced in TRPV1-deficient DRGs compared to wild-type (WT) DRGs. Significance: Repeated exposure to STW 5 induced desensitisation of sensory neurons and may ultimately contribute to its proven clinical efficacy against sensory-related symptoms in patients with FGID, including abdominal pain, bloating, nausea, and early satiety. This effect is modulated by the two prominent irritant sensors in nociceptors, TRPA1 and TRPV1.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Abdominal pain; Dorsal root ganglion; Functional gastrointestinal disorders; STW 5; Visceral hypersensitivity